Early Detection System for Stunting in Toddlers using an Arduino-based Ultrasonic Sensor based on Body Height - Syahbaniar Rofiah; Ade Kurniawan (LPPM Universitas Islam 45 Bekasi, 2025)
Stunting is a very important public health problem because it can have a big impact on a generation. One of them is the risk factor of nutrition and food intake that is not fulfilled in toddlers. For this reason, a system is needed to find out earlier the growth and development period of toddlers so that stunting symptoms can be detected as early as possible so that it can provide solutions to overcome these problems. The proposer's linkage from previous research in 2018 focusing on elementary school children and toddlers is included in the research roadmap from 2018-2028. For this reason, an early detection system is designed with the stages of designing a height measuring device, toddler weight using an ultrasonic sensor and information detecting stunting is displayed on an LCD screen integrated with Arduino. The software development method uses prototypes and testing for accuracy in toddler height using Mean Absolute Percentage Error (MAPE) with a value of 2% and from the results of testing 10 toddlers, there were 3 children in the stunted category.